Minimizing Septectomy for Endoscopic Transsphenoidal Approaches to the Sellar and Suprasellar Regions: A Cadaveric Morphometric Study - Garcia, Hermes G.; Otten, Marc; Pyfer, Marc; Singhal, Saurabh J.; Iloreta, Alfred Marc; Kshettry, Varun R.; Farrell, Christopher J.; Nyquist, Gurston; Rosen, Marc; Evans, James J. (Journal of Neurological Surgery Part B: Skull Base, 2016)
The purpose of this study was to evaluate the effect of posterior septectomy size on surgical exposure and surgical freedom during the endoscopic transsphenoidal approach to the sella and parasellar region. Dissections were performed on 10 embalmed cadaver heads. Dissections started with wide bilateral sphenoidotomies, lateralization of middle turbinates, and a 5-mm posterior septectomy. The posterior septectomy was increased in 5-mm increments to a maximum of 35 mm, followed by bilateral middle turbinectomies. Surgical exposure was defined as the distance between the ipsilateral and contralateral limit of exposure as allowed by the posterior septum along a midsphenoid horizontal meridian. Surgical freedom was defined as the angle between the ipsilateral and contralateral limit. The mean baseline width of the posterior sphenoid sinus was 29.4 ± 3.7 mm. With a 5-mm septectomy, the mean width of surgical exposure was 21.1 ± 2.8 mm. The surgical exposure increased significantly with progressively larger posterior septectomy until a 20-mm posterior septectomy, after which no further increase in surgical exposure or freedom was obtained. Bilateral lateral opticocarotid recesses were accessible with a 15-mm posterior septectomy. The addition of bilateral middle turbinectomies did not significantly increase lateral exposure within the sphenoid sinus compared with middle turbinate lateralization.
Keywords: endoscopic; endonasal; transnasal; transsphenoidal; septectomy; middle turbinectomy; sinonasal quality of life